The Guarantee of the Pledge of Development of “Safe Mahalla” Community Development - Rakhimov Ilkhomjon Azimjonovich (Periodica Journal, 2023)
The article conducting reforms and positive changes in Uzbekistan in recent years, and the importance of the Safe Mahalla System’s Self-Management "The advantages of the Mahallabay Working System in the implementation of the system is aimed at studying the concept of" Safe Mahalla "on crime prevention in the neighbourhoods. Methods of comparative-critical study and analysis of political, and pedagogical literature in research methods were used. The results of the study are given proposals in our country to introduce the introduction of the Safe Mahalla system
Keywords: On the organization of the activities of the Ministry of Support of Mahalla and the older generation; the concept of implementation of the principle of prosperous and safe proximity to 2020-2024; the Mahalla-the sector-the folk technique-the Mahalla